Micro-Finance Services and its Impact on Socio-economic Status of People in Gandaki Province, Nepal - Silwal, Sudarshan (Janapriya Journal of Interdisciplinary Studies, 2024)
The MFIs which offer financial services to empower and support to the underpriveledged individuals in grassroot level is called microfinance. This paper explores the pattern of microfinance service utilization and assess the socio-economic impact of microfinance service on its user groups in the Gandaki Provice of Nepal. This study has used the randam sampling techniques for the selection of study area. Mixed-method approach for the data collection and thematic as well as statistical software as the main tools of data analysis have been applied. The study found predominantly married female user groups with secondary level education and mainly dependent on agriculture and livestocks for their livelihoods. A significant portion of people have more than five year experience of using microfinance, majority of the respondents have made choice of all products, attained information of microfinance service from community based source, found seeking loans to expand their businesses. There is positive perception among the user groups with high satisfaction level, frequent usage of microfi nance products and positive impact on lifestyle, household income, pursuit of higher education basically women, access to healthcare for children and aged member of the groups, women participation in decision making and self-development of the members. But it is found notable concerns and challenges pertaining to high interest rates, loan repayment, reducing financial vulnerability and accumulating assets like house and land.